Use of Napsin-A, TTF-1, ER, GCDFP-15, GATA-3 and GATA-3 Markers to Differentiate Breast Metastasis from Lung Adenocarcinoma - Askari, Elham; Pourabdollah, Mihan; ahadi, mahsa; Daraei, Hasan (Student Research in Translational Medicine, 2023)
Background and Aim: Breast carcinomas with metastasis to lungs and primary lung adenocarcinomas have significant overlap. This study aimed to investigate the differential expression of a panel of IHC markers in primary lung adenocarcinomas and invasive ductal carcinomas (IDC) of the breast. Methods: In this cross sectional study, total of 50 specimens including 25 primary lung adenocarcinomas and 25 invasive ductal carcinomas of the breast were collected from Masih Daneshvari and Shohada-e-Tajrish hospitals. After all of the cases were stained with hematoxylin - and - eosin, the histologic diagnosis and grading of the slides were reviewed and reported by experienced pathologists based on standard classifications. The patients’ medical records were reviewed for demographic data, clinical information and histopathologic reports. Results: The median age of the patients with lung adenocarcinoma and IDC was 59 (32-78) and 50 (35-74) years, respectively. In this study, regarding lung adenocarcinomas, the most common type was acinar (56%), followed by solid (20%), mucinous (16%), lepidic (4%), and colloid (4%). Immunohistochemical expression for Napsin-A, TTF-1, ER, GCDFP-15, and GATA-3 in primary lung adenocarcinomas and invasive ductal carcinomas of the breast were different. Conclusion: Napsin-A, TTF-1, ER, GCDFP-15, GATA-3 and GATA-3 Markers can differentiate the breast cancer from lung adenocarcinoma. Napsin-A and TTF1 only present in lung adenocarcinoma.